The cultural logic of politics in mainland China and Taiwan - Shi, Tianjian (Cambridge University Press, 2015)
"This title uses surveys, statistics, and case studies to explain why and how cultural norms affect political attitudes and behavior"-- Provided by publisher
Keywords: Politics and culture -- China.; Politics and culture -- Taiwan.; Political culture -- China.; Political culture -- Taiwan.; Political sociology.; Politique et culture -- Chine.; Politique et culture -- Taiwan.; Sociologie politique.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; Political culture; Political sociology; Politics and culture; China; Taiwan